A Multi-Polarization Enabled Generalized Joined Coupler (MPE-GJC) Matrix for Multi-Beam Antenna Arrays - Zeng, Fan Chao; Li, Ming; Ding, Can; Jay Guo, Y. (IEEE transactions on antennas and propagation, 2025)
This communication presents a novel multi-polarization enabled Generalized Joined Coupler (MPE-GJC) matrix designed for multibeam and multi-polarization antenna arrays. Multiple beams can be generated simultaneously, with each beam's pointing direction independently configured. Each beam can adopt the same or different polarizations, arbitrarily selected from horizontal, vertical, left-hand circular, and right-hand circular polarizations. We propose two optimization methods-excitation vector optimization (EVO) and joint-beam multi-objective (JBMO) optimization-balancing computational efficiency and system performance. A 4×20 MPE-GJC matrix was optimized using both methods and used to feed a 1×10 dual-polarized antenna array. Active radiation patterns of each antenna element, obtained through full-wave simulation, were employed to accurately assess the matrix's beamforming capability. The results demonstrate that the four beams' polarizations and main directions can be independently configured by adjusting only the phase shifter values. This provides a new solution to support both terrestrial and non-terrestrial communication for 6G simultaneously, where linear and circular polarizations are desired, respectively.